The benefits of being a bit of an asshole. (1st September 2014) - Schrag, Anthony
In the United Kingdom, over the past decade, Socially Engaged practices have been variously employed to eradicate conflict and produce artworks that are diverse, multiple, all-welcoming and that smooth the turbulence of social tensions. Conflict, however, is an integral part of the social realm and to deny its presence is to deny the true functioning of a democratic realm. What, then, is the role of conflict within public and participatory artworks?